IMPACT OF THE COVID-19 PANDEMIC ON THE PRICE AND VOLUME OF STOCK TRANSACTIONS IN HOSPITALS IN INDONESIA - Pelinta Tarigan; Silvia Christelia; Ingkak Chintya Wangsih; Yohana (Bajang Institute, 2021)
The aim of the study was to look at the comparison between stock prices and hospital transaction volume before and after the announcement of the first COVID-19 pandemic in Indonesia. The population in this study is a hospital listed on the Indonesia Stock Exchange (IDX). Samples in this study used purposive sampling techniques, hospital data obtained by as many as 6 companies listed on the Indonesia Stock Exchange (IDX), this study used paired sample t-test techniques and data process using SPSS version 26. The result of this study is the stock price of hospitals before and after the announcement of COVID-19 cases in Indonesia is very significant with sig value. (2tailed) the result is 0,000 (p < 0.05) meaning that significant changes (mean) and for the Volume of Hospital Transactions before and after the announcement of COVID-19 cases in Indonesia is very significant with sig value. (2 tailed) the result is 0.033 (p < 0.05) meaning a significant change (meaning).